Description and analysis of clinical pathways for oesophago-gastric adenocarcinoma, in 10 European countries (the EURECCA upper gastro intestinal group – European Registration of Cancer Care). Issue 9 (September 2016) - Messager, M.; de Steur, W.; Boelens, P.G.; Jensen, L.S.; Mariette, C.; Reynolds, J.V.; Osorio, J.; Pera, M.; Johansson, J.; Kołodziejczyk, P.; Roviello, F.; De Manzoni, G.; et al.
Abstract: Aims: Outcomes for patients with oesophago-gastric cancer are variable across Europe. The reasons for this variability are not clear. The aim of this study was to describe and analyse clinical pathways to understand differences in service provision for oesophageal and gastric cancer in the countries participating in the EURECCA Upper GI group. Methods: A questionnaire was devised to assess clinical presentation, diagnosis, staging, treatment, pathology, follow-up and service frameworks across Europe for patients with oesophageal and gastric cancer. The questionnaire was issued to experts from 14 countries. The responses were analysed quantitatively and qualitatively and compared. Results: The response rate was (10/14) 71.4%. The approach to diagnosis was similar. Most countries established a diagnosis within 3 weeks of presentation. However, there were different approaches to staging with variable use of endoscopic ultrasound reflecting availability. There has been centralisation of treatments in most countries for oesophageal surgery. The most consistent area was the approach to pathology. There were variations in access to specialist nurse and dietitian support. Although most countries have multidisciplinary teams, their composition and frequency of meetings varied. The two main areas of significant difference were research and audit and overall service provision. Observations on service framework indicated that limited resources restricted many of the services. Conclusion: The principle approaches to diagnosis, treatment and pathology were similar. Factors affecting the quality of patient experience were variable. This may reflect availability of resources. Standard pathways of care may enhance both the quality of treatment and patient experience.